Spiritual emotional freedom technique (seft) to reduce the diabetes distress in people with diabetes mellitus - Priyanto, Wardiani; Widyana, Rahma; Verasari, Metty (Indigenous, 2021)
This study aimed to examined the effectiveness of Spiritual Emotional Freedom Technique (SEFT) for Healing to reduce the diabetes distress levels in people with diabetes mellitus at productive age. Participant in this study were 12 people, 33-61 years old male and female with moderate and high levels of diabetes distress as measured with diabetes distress scale/ DDS17. This research design was an experimental pre-post-test control group design with exeperimental group and control group. The data analysis technique used in this study was statistical analysis with the Wilcoxon sign rank test and the Mann whitney U-test. The results of the Wilcoxon Sign Rank Test showed a significance value of p= 0.028 (p 0.05) and was strengthened by the results of the Mann Whitney U-Test with a significance value of p= 0.004 (p 0.05) and a decrease in the value of x̅ = 63.33 to x̅ = 20.33, which means there is a significant difference in the level of diabetes distress in people with diabetes mellitus at productive age before and after being given the SEFT for Healing intervention. These results indicate that SEFT for Healing can reduce the level of diabetes distress and the hypothesis is accepted. SEFT for healing is proven effective and can be used as one of the therapy to reduce the distress in people with diabetes.